2014
DOI: 10.1038/jp.2014.164
|View full text |Cite
|
Sign up to set email alerts
|

Early radiologic evidence of severe respiratory distress syndrome as a predictor of nasal continuous positive airway pressure failure in extremely low birth weight newborns

Abstract: Early radiologic evidence of severe RDS is predictive of CPAP failure, especially in infants with GA ⩽ 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
0
37
1
Order By: Relevance
“…Data from several hospital-based cohort studies strongly suggest that CPAP failure is primarily caused by untreated surfactant deficiency, and is associated with adverse outcomes, including increased risk of mortality as well as morbidities, including air leak, bronchopulmonary dysplasia (BPD), and intraventricular hemorrhage (IVH). [9][10][11][12][13][14] Reported studies of CPAP failure have involved relatively small cohorts of infants managed at 1 or 2 centers. [9][10][11][12][13][14] Examination of the effects of initial CPAP support and CPAP failure within largescale neonatal databases has been hampered by difficulty in identifying the exact sequence of respiratory management in early life within the reported data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several hospital-based cohort studies strongly suggest that CPAP failure is primarily caused by untreated surfactant deficiency, and is associated with adverse outcomes, including increased risk of mortality as well as morbidities, including air leak, bronchopulmonary dysplasia (BPD), and intraventricular hemorrhage (IVH). [9][10][11][12][13][14] Reported studies of CPAP failure have involved relatively small cohorts of infants managed at 1 or 2 centers. [9][10][11][12][13][14] Examination of the effects of initial CPAP support and CPAP failure within largescale neonatal databases has been hampered by difficulty in identifying the exact sequence of respiratory management in early life within the reported data.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] Reported studies of CPAP failure have involved relatively small cohorts of infants managed at 1 or 2 centers. [9][10][11][12][13][14] Examination of the effects of initial CPAP support and CPAP failure within largescale neonatal databases has been hampered by difficulty in identifying the exact sequence of respiratory management in early life within the reported data. 15 Populationbased data on the incidence of, and outcomes after, CPAP failure would give clarity on the magnitude of the problem, both overall and within gestation strata.…”
mentioning
confidence: 99%
“…NCPAP failure is associated with the need for invasive MV, development of BPD and death. No consensus exists regarding the criteria used to characterize NCPAP failure, which is variably defined in studies, and neonatal units may have different success rates based on how NCPAP is applied at the bedside . However, different success rates in neonatal units have been reported, based on their experience with NCPAP use .…”
Section: Discussionmentioning
confidence: 99%
“…No consensus exists regarding the criteria used to characterize NCPAP failure, which is variably defined in studies, and neonatal units may have different success rates based on how NCPAP is applied at the bedside. [25][26][27] However, different success rates in neonatal units have been reported, based on their experience with NCPAP use. 4,28 The failure criteria for noninvasive ventilation used in this study correspond to our historical NCPAP failure rate of 40% to 50% among VLBW infants and are very similar to those used in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have reported on the usage of intubation and surfactant therapy in moderate to late preterm infants. [12][13][14] However, there are no clear guidelines regarding indications for endotracheal intubation in moderate to late preterm infants of 32-36 weeks gestation. Hence, we conducted a survey of neonatologists in Australia and New Zealand to understand the current practice of clinicians in this area.…”
Section: Introductionmentioning
confidence: 99%